Tilt engineering of exchange coupling at G-type SrMnO3/(La,Sr)MnO3 interfaces - Li, F.; Song, C.; Wang, Y. Y.; Cui, B.; Mao, H. J.; Peng, J. J.; Li, S. N.; Wang, G. Y.; Pan, F. (Scientific reports, 2015)
With the recent realization of hybrid improper ferroelectricity and room-temperature multiferroic by tilt engineering, “functional” octahedral tilting has become a novel concept in multifunctional perovskite oxides, showing great potential for property manipulation and device design. However, the control of magnetism by octahedral tilting has remained a challenging issue. Here a qualitative and quantitative tilt engineering of exchange coupling, one of the magnetic properties, is demonstrated at compensated G -type antiferromagnetic/ferromagnetic (SrMnO 3 /La 2/3 Sr 1/3 MnO 3 ) interfaces. According to interfacial Hamiltonian, exchange bias (EB) in this system originates from an in-plane antiphase rotation ( a − ) in G -type antiferromagnetic layer. Based on first-principles calculation, tilt patterns in SrMnO 3 are artificially designed in experiment with different epitaxial strain and a much stronger EB is attained in the tensile heterostructure than the compressive counterpart. By controlling the magnitude of octahedral tilting, the manipulation of exchange coupling is even performed in a quantitative manner, as expected in the theoretical estimation. This work realized the combination of tilt engineering and exchange coupling, which might be significant for the development of multifunctional materials and antiferromagnetic spintronics.